Hallazgo de un nido de Chorlito de Vincha (Phegornis mitchelli) en Mendoza, Argentina - Fernandes d'Oliveira, Gustavo; Rodríguez Moulin, Horacio (El Hornero, 1997)
Este artículo no cuenta con un resumen.